Reproductive immunology - Gupta, S. K. (Satish K.); National Institute of Immunology (India); International Congress on Reproductive Immunology 1998 : New Delhi, India) (New Delhi : Narosa Pub. House, 1999)
Papers presented at the VII International Congress of Reproductive Immunology held from 27-30 October 1998, New Delhi; organised by National Institute of Immunology.
Includes bibliographical references and indexes.
Keywords: Reproduction -- immunology; Pregnancy Complications -- immunology; Infertility -- immunology